Efficacy of Unsupervised Home-Based Pulmonary Rehabilitation for Patients with Chronic Obstructive Pulmonary Disease - Lee, Jang Ho (Int J Chron Obstruct Pulmon Dis, 2020)
PURPOSE: Pulmonary rehabilitation (PR) is a well-established treatment for chronic obstructive pulmonary disease (COPD). The standard protocol for PR requires frequent hospital visits, which can be difficult for patients. We performed this study to assess whether unsupervised home-based PR (HBPR) is effective for patients with COPD. PATIENTS AND METHODS: After assessing the outcome data, including the results of a COPD assessment test (CAT); the body mass index, airflow obstruction, dyspnea, and exercise capacity (BODE) index; a spirometry; the modified Medical Research Council (mMRC) dyspnea scale; and the 6-min walking test (6MWT), specialists imparted 1-hour education to patients regarding unsupervised HBPR at the baseline visit. This included methods for breathing, inhaler use, stretching, and exercise. On reviewing diaries after 8 weeks from the first visit, patients who exercised at least thrice per week were classified as the compliant group and the others were categorized as the noncompliant group. Changes in the outcomes were compared between the compliant and noncompliant groups. RESULTS: A total of 41 patients were enrolled in this study; for 8 weeks of unsupervised HBPR, there were significant improvements in CAT scores (−4.62±4.61 vs 2.40±6.73; P=0.002), BODE index (−1.00±1.06 vs −0.20±0.56; P=0.01), and forced expiratory volume in 1 s (0.05±0.19 vs −0.09±0.16; P=0.02) among patients in the compliant group, compared with the noncompliant group. Moreover, their CAT (16.46±7.80 vs 11.85±7.23; P=0.03) and mMRC scores (2.54±0.76 vs 1.81±0.63; P=0.001) improved significantly after 8 weeks, compared with those at baseline. On the other hand, patients in the noncompliant group showed no significant improvement in any of the outcomes. CONCLUSION: In this study, compliant patients with unsupervised HBPR achieved favorable outcomes in 8 weeks. Thus, we recommend unsupervised HBPR for patients with COPD, even when regular hospital visits for PR are not possible. TRIAL REGISTRATION: NCT03754881.